Training Need Assessment on Communication Competencies of Extensionists working in Krishi Vigyan Kendras (Farm Science Centres) - Rohit, Jagriti; C.N, Anshida Beevi (Journal of Extension Education, 2018)
Training need assessment has always been an important area in the designing the capacity development programme for the extensionists. It helps to make the extensionists updated, upgraded and competent in their field. Training need using Borich Need Assessment Model was carried out in the four zones of Krishi Vigyan Kendras (KVK) to assess the communication competencies of the extensionists. The zones of KVKs were selected using simple random sampling without replacement method. From each zone, 20 KVKs were selected randomly and 3 extensionists from each KVK were selected by using simple random sampling technique. The total sample size was 240. Mean weighted discrepancy score (MWDS) was used to study the training needs. The results of the study indicated that the highest level of training need was expressed in their ability to use computer (Internet) and PowerPoint presentation followed by their “ability to prepare visual aids to help deliver information” while lowest mean weighted discrepancy score was given to their ability in presenting the seminar. Kruskal wallis test was carried out to find the differences among the zones of KVK. Attention should be given to designing inservice training programmes which can adequately address the present training needs of the extensionists.